The use of rh-NGF in the management of neurotrophic keratopathy - Roszkowska, Anna M.; Spinella, Rosaria; Calderone, Alessandro; Sindoni, Marianna; Wowra, Bogumił H.; Kozak, Maciej; Sajak-Hydzik, Katarzyna; Aliò, Jorge (Frontiers in Ophthalmology, 2024)
Neurotrophic keratitis or keratopathy (NK) is a degenerative corneal disease induced by impairment of the trigeminal nerve function. This condition may lead to persistent epithelial defects, corneal ulceration, and perforation. The diagnosis of NK requires a careful investigation of any ocular and systemic condition associated with the disease and ocular surface and corneal sensitivity examinations. In the past, several medical and surgical procedures were used to treat this condition with different clinical effectiveness. Cenegermin is a recombinant human nerve growth factor (rh-NGF) that supports corneal reinnervation. Different clinical trials have demonstrated the safety and efficacy of topical cenegermin in patients with moderate to severe neurotrophic keratitis. In this review, we report the literature on clinical results regarding the treatment of NK with cenegermin since its approval by the European Medicines Agency (EMA) and the Food and Drug Administration (FDA) in 2017 and 2018, respectively.